Health, Lifestyle, and Gender Influences on Aging Well: An Australian Longitudinal Analysis to Guide Health Promotion - Kendig, Hal; Browning, Colette J.; Thomas, Shane A.; Wells, Yvonne (Frontiers in Public Health, 2014)
A primary societal goal for aging is enabling older people to continue to live well as long as possible. The evidence base around aging well (“healthy,” “active,” and “successful” aging) has been constructed mainly from academic and professional conceptualizations of mortality, morbidity, functioning, and psychological well-being with some attention to lay views. Our study aims to inform action on health promotion to achieve aging well as conceptualized by qualitative research identifying what older Australians themselves value most: continuing to live as long as possible in the community with independence in daily living, and good self-rated health and psychological well-being. Multivariate survival analyses from the Melbourne longitudinal studies on healthy aging program found that important threats to aging well for the total sample over a 12-year period were chronological age, multi-morbidity, low perceived social support, low nutritional score, and being under-weight. For men, threats to aging well were low strain, perceived inadequacy of social activity, and being a current smoker. For women, urinary incontinence, low physical activity and being under-weight were threats to aging well. The findings indicate that healthy lifestyles can assist aging well, and suggest the value of taking gender into account in health promotion strategies.